2010
DOI: 10.1007/s12032-010-9586-0
|View full text |Cite
|
Sign up to set email alerts
|

Berberine-induced apoptosis via decreasing the survivin protein in K562 cell line

Abstract: Berberine is an isoquinoline alkaloid with multiple pharmacological activities, including anti-inflammatory and anti-diarrhea effect, the induction of apoptosis and anti-cancer effect. It has been reported that berberine exerts its anti-inflammatory effect via suppressing nuclear factor-kappa B (NF-κB) expression. Survivin and inducible nitric oxide synthase (iNOS) proteins may contribute to the causal relationship between anti-inflammatory and anti-apoptotic function. To investigate the mechanism of berberine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Survivin is an anti‐apoptotic protein, overexpression of survivin was observed in several tumor cells (Altieri, ; Altieri, ; Pazhang et al, ). To further dissect the possible CP mechanism of action, the survivin protein level in treated and untreated LNCaP cells was evaluated by immunocytochemistry and immunoblotting techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survivin is an anti‐apoptotic protein, overexpression of survivin was observed in several tumor cells (Altieri, ; Altieri, ; Pazhang et al, ). To further dissect the possible CP mechanism of action, the survivin protein level in treated and untreated LNCaP cells was evaluated by immunocytochemistry and immunoblotting techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Survivin is a bifunctional inhibitor of apoptosis (IAP) that has been implicated in the protection against apoptosis and promoting mitosis (Dohi et al, ). It is well‐established that survivin is expressed in most human cancers and has recently attracted a great attention as a potential candidate for cancer therapy (Altieri, ; Altieri, ; Pazhang et al, ). Moreover, it is determined that survivin mediates resistance to antiandrogen therapy in prostate cancer cell lines including LNCaP, PC‐3, and DU‐145 and interestingly all three cell lines were found to strongly express survivin.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, one study demonstrated that berberine induced apoptosis in breast, liver, and hematopoietic cancer cells through mitochondrial‐dependent manner by increasing levels of caspase‐3 and 8 activity and decreasing expression of caspase inhibitors such as survivin and Bcl‐2 (Marschitz et al, 2000; Patil, Kim, & Jayaprakasha, 2010; Pazhang, Ahmadian, Mahmoudian, & Shafiezadeh, 2011; Yip & Ho, 2013). Furthermore, results demonstrated that berberine leads to up‐regulation of p53 as an apoptotic inducer protein, while without affecting the normal breast epithelial cell growth at 25 μM concentration (Patil et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Berberine has low toxicity to healthy cells and high cytotoxicity to cancer cells, which makes its research in anticancer become the most promising. Since the rst study on the cytotoxicity in cancer cells of berberine in 1986 7 , its anticancer properties have been proved in many cancer cell studies [8][9][10][11][12] , which makes berberine one of the most interesting and promising natural anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%